Development Planning and Forecasting Fleet of Tractors and Grain Harvesters of the Agro-Industrial Complex of the Republic of Kazakhstan - Kulmukhanbet, Akhmetov; Galizhan, Madiev; Gulnara, Seydalieva; Assel , Bekbossynova; Gulsim , Aitkhozhaeva (Journal of Ecohumanism, 2024)
The methodological provisions on the justification and forecasting by the method of astrological modeling of the needs of the agro-industrial complex of Kazakhstan in agricultural machinery for plant growing on the basis of data of tractors and combine harvesters are given in the work. Prepared within the framework of the grant Project of the State Institution “Science Committee” of the Ministry of Education and Science of the Republic of Kazakhstan on topic No. AP19678876 “Effective system of macroeconomic instruments for state regulation of innovative development of the agro-industrial complex of the Republic of Kazakhstan”